1974
DOI: 10.1901/jeab.1974.22-311
|View full text |Cite
|
Sign up to set email alerts
|

GROUP BEHAVIOR OF RATS UNDER SCHEDULES OF REINFORCEMENT1

Abstract: Groups of three rats were placed in a chamber containing one response lever and one water dispenser. A variety of schedule conditions were explored including fixed ratio, extinction, satiation, fixed interval, fixed time, differential reinforcement of low rates, and discrimination learning. Each group was treated as a single unit, with the collective lever responses emitted by the three rats being the main dependent variable. Group responding was found to be controlled by the reinforcement schedules in an orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The most important development has been the use of token economies (e.g., Ayllon and Azrin, 1968), sometimes explicitly linked to an economic analysis (Winkler, 1971), and of multi-operant environments (e.g., Findley, 1966). But much more could be done, along the lines of applying economic concepts to standard operant paradigms (as in Green and Rachlin, 1975, or Kagel, Battalio, Rachlin, Green, Basmann, and Klemm, 1975), or showing that phenomena known in individuals also apply to groups (as in Grott and Neuringer, 1974). The present experiments have shown that both these last strategies can be pursued simultaneously.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The most important development has been the use of token economies (e.g., Ayllon and Azrin, 1968), sometimes explicitly linked to an economic analysis (Winkler, 1971), and of multi-operant environments (e.g., Findley, 1966). But much more could be done, along the lines of applying economic concepts to standard operant paradigms (as in Green and Rachlin, 1975, or Kagel, Battalio, Rachlin, Green, Basmann, and Klemm, 1975), or showing that phenomena known in individuals also apply to groups (as in Grott and Neuringer, 1974). The present experiments have shown that both these last strategies can be pursued simultaneously.…”
Section: Discussionmentioning
confidence: 76%
“…On the one hand, some schedule effects survive relaxation of standard experimental conditions. Grott and 183 1977, 25, 183-194 NUMBER I (JANUARY) Neuringer (1974) showed that a group of rats behaves roughly like a single rat on some standard schedules of reinforcement; Morgan, Fitch, Holman, and Lea (1976) used multipleinterval schedules to teach higher-order concepts to free-living pigeons with unrestricted access to the schedules; and Baum (1972Baum ( , 1974a obtained matching from a single pigeon with unrestricted access to conc VI VI, and from free-living pigeons with virtually unrestricted access (only one pigeon could occupy the apparatus at a time). On the other hand, if different subjects can command two manipulanda, the situation might approximate a simple, rather than a concurrent schedule: as soon as reinforcement is available on each schedule, it might be taken by the subject commanding the corresponding manipulandum.…”
mentioning
confidence: 99%
“…Analogously, merely permitting varied social behavior, as in a free or laissezfaire society, may not suffice to produce the desired diversity. If the results, shown for individual organisms, can provide useful information for groups (see, e.g., Grott & Neuringer, 1974), then when variations are desired, societies might reward individuals for varying, not simply permit it.…”
Section: Implications For Societymentioning
confidence: 99%
“…Grott and Neuringer (1974) used this procedure to determine the effects of discrimination training procedures and schedules of reinforcement, and the same approach was employed in the analysis of a group living and worksharing system for college students (Feallock & Miller, 1976). Of considerable practical importance is the experimental literature on the application of group contingencies in business and industry.…”
Section: Contingencies Of Reinforcementmentioning
confidence: 99%